Psychological Factors Affecting Pain Response in Critically Ill Patients: A Narrative Literature Review - Rani Iswara (HM Publisher, 2021)
Critical illnesses are usually painful, both because of the underlying source of the disease and the necessary procedures performed to monitor and care for these patients. This literature review aimed to describe psychological factors affecting pain response in patients. Pain induces anxiety, sleep deprivation, disorientation, agitation, delirium and often becomes chronic depression. Psychological factors (sleep deprivation, anxiety, and delirium) can also increase the perception of pain. Pain assessment is required for proper pain management. Opioids are commonly used in pain management, but acetaminophen, dexmedetomidine, and gabapentin have more advantages. The recent trend is multimodal analgesia, which uses a combination of analgesic drugs with different mechanisms of action. Another trend is the increasing use of pain relievers, which can control pain and relieve anxiety. In conclusion, physiological factors are the cause and effect of pain in critically ill patients. In intensive care patients, anxiety, delirium, and lack of sleep can increase pain sensitivity.